Thermodynamic Studies for the Interaction of Some Anticoagulant Drugs with Albumin - Al-Rufaie, Elham M; Al-Shareefi, Zahraa H (Al-Nahrain Journal of Science, 2018)
Fluorescence spectroscopy in combination with UV- vis absorption spectroscopy was employed to investigate the binding of some important anticoagulant drugs warfarin, heparin and aspirin to human serum albumin under physiological conditions. Scatchard equation provide a measure of the binding affinity between these three drugs individually and albumin. The results of thermodynamic parameters ∆G, ∆H, and ∆S at three different temperatures indicate that the hydrophobic interaction plays a major role for the interaction between each of these drugs and albumin.